Response of phosphine-resistant and –susceptible Lasioderma serricorne adults to different light spectra. (May 2021) - Baliota, Georgia V.; Athanassiou, Christos G.; Cohnstaedt, Lee W.
Abstract : Laboratory studies were conducted to evaluate the behavior of adults belonging to two different populations of the cigarette beetle, Lasioderma serricorne (F.) (Coleoptera: Anobiidae), one resistant and one susceptible to phosphine, towards specific LED light stimuli. This was done in conjunction with other factors, such as sex and mating, as well as the presence or absence of food. For this purpose, LED lights with wavelength of 400 nm (ultraviolet, UV), 460 nm (blue), 505 nm (green) and 660 nm (red) were incorporated in a structure made of transparent acrylic plastic, which served as an arena, while the response of the adults to the visual cues was recorded 24 h after their release. The attractiveness of the UV light was consistently higher than the other spectra, regardless of the population, sex, mating status and the presence of food. We observed that the unmated males of the susceptible population showed a stronger flight response towards UV light compared with the unmated females that had responded to a lower degree, regardless of the presence of food. When mated adults of both sexes were released together in the arena, both populations had similar responses towards the light colors. Considering our findings, for the vast majority of the parameters tested, the natural behavioral variation in photo-attraction was not affected by phosphine resistance. The evaluation of the phototactic responses in L. serricorne is of major importance, as light and pheromone traps for monitoring of the activity of this species have been widely adopted globally in different types of storage and processing facilities of durable commodities. Highlights: Phosphine-susceptible and –resistant adults of Lasioderma serricorne had similar phototactic responses. Ultra violet (UV) spectra was the most attractive for L. serricorne. UV light spectra was effective on attracting unmated males and mated females. Food availability does not alter phototactic response in L. serricorne. Abstract.